The Problem of the Terror Non-State: Rescuing International Law from ISIS and Boko Haram - Johnson, Darin E.W. (2019)
This article examines how terror non-states, such as ISIS and Boko Haram, blur the distinctions between non-state actors and states under international law. Terror non-states’ confounding of this dichotomy undermines the efficacy of international human rights law in the territories that they control, complicates responsive foreign military intervention, and confuses the appropriate legal framework that governs armed conflicts in which they are involved. This article assesses these challenges and makes recommendations from a perspective that gives primacy to the protection and liberation of vulnerable populations. The article recommends that the United Nations Security Council pass a resolution that mandates that terror non-states comply with state-assumed international human rights obligations in the territories that they control. The article also determines that terror non-states’ destructive foreign attacks subject them to responsive foreign military intervention. The article further concludes that terror non-states’ oppression of vulnerable populations eliminates any potential claim that they are entitled to armed combatant immunity from domestic law during armed conflict. Finally, the article recommends that the United Nations establish an international tribunal for war crimes and human rights violations committed by ISIS, that Boko Haram leaders be referred to the International Criminal Court, and that the international community enhance its cooperation and support for the domestic prosecution of ISIS and Boko Haram